Structural design and optimization of a solar spouted bed reactor of biomass gasification. (25th July 2021) - Li, Xiaojing; Yan, Pengpeng; Ma, Chaofan; Wang, Jiangjiang
Highlights: A solar spouted bed reactor of biomass steam gasification is proposed. The simulation model of solar gasifier is constructed. The gasifier structures are optimized to improve gasification performance. The distributions of temperature and syngas are observed qualitatively. 92.29% of the gasification efficiency is obtained. Abstract: The structures of biomass gasifier are essential to the performance of gasification. This paper proposed a solar spouted bed reactor of biomass gasification, in which solar energy replaces the combustion self-heating of traditional gasifier. The key structural parameters of gasifier, such as the ratio of bottom diameter of conical contactor to oxidant inlet diameter, the ratio of oxidant inlet diameter to biomass particle average diameter and contact angle, the diameter and height of reactor, were optimized corresponding to the best gasification performance through the two-dimensional simulations by computational fluid dynamics software. A finite rate micro mixing model under chemical equilibrium was adopted to simulate the gasification reaction. The effects of these parameters on syngas composition, temperature, lower heating value, carbon conversion and gasification efficiency were explored by controlling single variable method and qualitative and quantitative analysis. When the structure of the gasifier is optimal, the lower heating value is 11.93 MJ/m 3, and the carbon conversion and biomass gasification efficiencies are 86.69% and 96.40%, respectively. The research results can provide an important reference for the future industrial design and application of solar biomass gasifier.